The Craft of Oblivion : Forgetting and Memory in Ancient China. - Galvany, Albert (State University of New York Press, 2023)
"The Craft of Oblivion" is an innovative and groundbreaking volume that aims to study, for the first time, the intersections between forgetting and remembering in classical Chinese civilization. Oblivion has tended to be relegated to a marginal position, often conceived as the mere destructive or undesirable opposite of memory, even though it performs an essential function in our lives. Forgetting and memory, far from being autonomous and mutually exclusive spheres, should be seen as interdependent phenomena. Drawing on perspectives from history, philosophy, literature, and religion, and examining both transmitted texts and excavated materials, the contributors to this volume analyze various ways of understanding oblivion and its complex and fertile relations with memory in ancient China.